(untitled) (Biological Sciences - PJSIR, 1999)
The lipase and phospholipase extracted fromthemealof matureseeds of Citrullusvulgarisshowedoptimumactivity at40°C and pH 7 in aqueous media. N-heptane was found to be themost satisfactory solvent media tomaximize activities of lipase and phospholipase. The activity of lipase extracted fromgerminated seeds increased with the stage of seeds development but was found to be reverse for the phospholipase activity.